Epistemology of Ngelmu in Wedhatama Fibers - Alfiana, Nur (International Proceedings of Nusantara Raya, 2022)
The purpose of this study is to uncover the epistemology of ngelmu in Wedhatama Fiber. Science and ngelmu in Javanese tradition are different. If science is rational and intellectual, it is more ruhaniah, high value, and becomes the basis of human behavior. This research method is qualitative. Data obtained through literature studies. Journals and books that discuss ngelmu in Serat Wedhatama become databases and analyses. The result of this study is that in Serat Wedhatama, ngelmu is also not limited to theory and intellectuals alone, but a practice that is aware of the noble values of teachings (piwulang). Between science and deeds must be balanced. People who try to find ngelmu (makrifat) by going through suluk or Sufism are called Sufis or mystics.